Optimization of anodization parameters in Ti-30Ta alloy - Capellato, Patricia (2020)
The current metallic biomaterial still presents failures associated with the bulk alloy and the interface of material/human body. In previous studies, titanium alloy with tantalum showed the elastic modulus decrease in comparison with that of commercially pure (cp) titanium. In this study, surface modification on Ti-30Ta alloy was investigated. Titanium and tantalum were melted, homogenized, cold-worked by a rotary swaging process and solubilized. The anodization process was performed in electrolyte contained glycerol + NH4F 0.25% at 30 V using seven different durations-4 h, 5 h, 6 h, 7 h, 8 h, 9 h, and 10 h and annealed at 530 °C for 1 h. The surface topography was characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM) measurements, X-ray diffraction analysis (XRD), and contact angle. From the results, we conclude the time of anodization process influences the shape and morphology of the anodized layer. The 5 h-anodization process produced a smooth and porous surface. The 4-, 6-, 7-, 8-, 9-, and 10-h conditions showed nanotubes morphology. All surfaces are hydrophilic (<90). Likewise, all the investigated conditions present anatase phase. So, this surface modification presents potential for biomedical application. However, more work needs to be done to better understand the influence of time on the anodization process.